Trends in lung cancer incidence in Iraq during the period 2005-2019 - M. Al-Hashimi, Muzahem; Yahya Al-Awjar, Muhammed Qasim (International Journal of Public Health Science (IJPHS), 2024)
Lung cancer, a prominent global malignancy and a significant contributor to cancer-related deaths, was examined in Iraq from 2005 to 2019 using data from the cancer registry. Age-standardized incidence rates (ASIR), categorized by sex and age at diagnosis, were analyzed to identify trends, utilizing annual percent change (APC) and average annual percent change (AAPC). During the 2005-2019 period, ASIR was 18.339/100,000 for males and 5.861/100,000 for females. Lung cancer ASIR experienced a notable 48.027% increase, starting at 9.426/100,000 in 2005 and reaching 13.953/100,000 in the most recent year. The rates demonstrated significant growth, with AAPC values of +2.857% for both sexes, +2.495% for males, and +4.474% for females. The highest incidences of lung cancer were among the elderly (70+ years) in both sexes, particularly pronounced in females (8.961%) and males (5.601%). In contrast, the lowest rates were found in individuals aged 0 to 49 years, showing negative APC values: -1.359% (males) and -0.843% (females). The study underscores the escalating prevalence of lung cancer in Iraq, particularly impacting older females. Urgent and targeted efforts are necessary to mitigate the rising incidence rates.